GSK-3 in Neurodegenerative Diseases. (18th April 2011) - Lei, Peng; Ayton, Scott; Bush, Ashley I.; Adlard, Paul A.
Abstract : Glycogen synthase kinase-3 (GSK-3) regulates multiple cellular processes, and its dysregulation is implicated in the pathogenesis of diverse diseases. In this paper we will focus on the dysfunction of GSK-3 in Alzheimer's disease and Parkinson's disease. Specifically, GSK-3 is known to interact with tau, β -amyloid (A β ), and α -synuclein, and as such may be crucially involved in both diseases. A β production, for example, is regulated by GSK-3, and its toxicity is mediated by GSK-induced tau phosphorylation and degeneration. α -synuclein is a substrate for GSK-3 and GSK-3 inhibition protects against Parkinsonian toxins. Lithium, a GSK-3 inhibitor, has also been shown to affect tau, A β, and α -synuclein in cell culture, and transgenic animal models. Thus, understanding the role of GSK-3 in neurodegenerative diseases will enhance our understanding of the basic mechanisms underlying the pathogenesis of these disorders and also facilitate the identification of new therapeutic avenues.